Analisis Kinerja Pengelolaan Sampah Kota Palangka Raya - Muhammad Arif Fathuddin Hamdie; Adi Jaya; Evi Veronika Elbaar; Herry Redin; Ici Piter Kulu; Dehen Erang (Jurnal Kaharati, 2021)
In the city of Palangka Raya with a population of 266,000 people, waste is a problem, among others, due to the limited facilities and infrastructure to support waste transportation. The average amount of waste transported by the Palangka Raya City Garbage Transport Team only reached 48.94% of the total waste that must be transported every month which reached 27,628.2 m³. Thus, the rate of waste production is still faster than efforts to overcome it. The purpose of this research is to study the performance of waste management in Palangka Raya City from the generation of waste, support for financing, and regulation, as well as to study the priority aspects as supporting the performance of waste management so that waste management can improve and the aspects that are the main causes and can affect the management performance of waste, as well as how the planning and commitment of the Palangka Raya City government towards improving the performance of waste management. The research method is quantitative descriptive, analysis of waste management performance data and priority setting is carried out with a Likert Scale modification. The number of respondents as many as 30 people who are all waste management supervisors in Pahandut and Jekan Raya Subdistricts which are the research locations. The results show that the value response in the form of a percentage that is considered appropriate requires priority handling, namely waste facilities (81%) as the first priority, financial support (70%) as the second priority, waste generation (69%) the third priority, regulation (65%) , and waste infrastructure (53%). In general, the performance of solid waste management in the City of Palangka Raya needs to be improved, especially in the waste facilities because the amount of waste generated in the City of Palangka Raya has not been balanced with the performance of waste management.